Late presentations of congenital myasthenic syndromes: How many do we miss?. Issue 4 (9th July 2016) - Garg, Nidhi; Yiannikas, Con; Hardy, Todd A.; Belaya, Katsiaryna; Cheung, Jonathan; Beeson, David; Reddel, Stephen W.
ABSTRACT: Introduction : Congenital myasthenic syndromes (CMS) usually present neonatally or in early childhood. When they present later, they may be mistaken for seronegative autoimmune myasthenia, and unnecessary immunosuppressive treatment may be administered. Methods : Patients who met criteria for seronegative generalized myasthenia without congenital or early childhood onset, but with an affected sibling were tested for CMS associated genes using exome and Sanger sequencing. Results : Four sibling pairs from nonconsanguineous families were identified. Three had mutations in the RAPSN gene, and 1 had a mutation in CHRNA1 . One sibling of a pair with symptoms of fatigue but no convincing features of neuromuscular dysfunction tested negative on genetic studies. The definite CMS cases comprised 7 of 25 seronegative patients with definite generalized myasthenia in the clinic, and over half had been treated for autoimmune myasthenia. Conclusions : CMS is probably underdiagnosed in seronegative myasthenic disorders and should be considered in the differential diagnosis. Muscle Nerve 54 : 721–727, 2016